EFEK PENAMBAHAN SERAT POLYPROPYLENE TERHADAP KUAT TEKAN BETON PADA PERKERASAN KAKU - Thariq Al Faridzi A Sultan; Ismanto Wahab Ali; Abdul Gaus; Mufti Amir Sultan (Jurnal Teknik Sipil : Rancang Bangun, 2023)
Rigid pavement or cement concrete pavement is a construction (pavement) with aggregate and raw materials and uses cement as a binding material. Rigid pavements have good compressive strength, but in contrast to flexural strength, this is due to their brittle nature, so when planning rigid pavements, fiber is added to the concrete mixture in the hope of increasing the elastic or flexible properties of the rigid pavement itself. This study aims to analyze the effect of adding polypropylene fibers to a mixture of rigid pavement concrete with a variation of 0.1%; 0.3%; 0.5%; 0.7%; and 1.0% by weight of cement. Control test objects without using polypropylene fiber. The number of cylindrical specimens of 15x30 cm was 30 pieces. Compressive strength test. The results showed that the compressive strength were optimum at 0.30%.